GAMBARAN DAYA LEDAK OTOT TUNGKAI PADA PESERTA EKSTRAKULIKULER BASKET DI SEKOLAH MENENGAH ATAS - Al Gifari, Muhammad Yusrin; Putri, Maulida Wijaya; Parulian Panjaitan, Arnold Fransimon (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2024)
Muscle explosiveness is the most important thing for basketball players, where someone uses maximum force deployed in the shortest or shortest time. Purpose of this study is to determine the distribution of age, gender, body mass index, and explosive power of basketball extracurricular participants at SMAN 2 Banjarmasin. Method: This study used quantitative descriptive method with vertical jump measuring instrument. The results of the study based on the most age at the age of 16 years as many as 15 people (53.57%), then at the age of 15 and 17 years each as many as 6 people (21.42%), and at the age of 18 years as many as 1 person (3.57%). The results of the study based on sex were most in the male sex as many as 16 people (57.14%), in the female sex as many as 12 people (42.85%). The results of the study were based on the most body mass index at the index of 18.5-22.9 as many as 16 people (57.14%) and 23-29.9 as many as 10 people (35.72%) while the least index was <18.5 and >30 as much as 1 (3.57%).The results of the study were based on muscle explosive power in the good and sufficient categories as many as 10 people (35.77%), very good categories as many as 4 people (14.78%), less categories 3 people (10.11%), while the perfect category was only 1 person (3.57%). Conclusion: For basketball players who still have the ability to explode leg muscles that are lacking, in order to improve it by routine training using plyometric exercises Keywords :Basketball, Muscle Explosive Power, Vertical jump.